2000
DOI: 10.1128/mcb.20.11.4149-4158.2000
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorylation of SOX9 by Cyclic AMP-Dependent Protein Kinase A Enhances SOX9's Ability To Transactivate aCol2a1 Chondrocyte-Specific Enhancer

Abstract: Sox9 is a high-mobility-group domain-containing transcription factor required for chondrocyte differentiation and cartilage formation. We used a yeast two-hybrid method based on Son of Sevenless (SOS) recruitment to screen a chondrocyte cDNA library and found that the catalytic subunit of cyclic AMP (cAMP)-dependent protein kinase A (PKA-C␣) interacted specifically with SOX9. Next we found that two consensus PKA phosphorylation sites within SOX9 could be phosphorylated by PKA in vitro and that SOX9 could be ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
168
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(176 citation statements)
references
References 35 publications
7
168
1
Order By: Relevance
“…Some genes listed in Table 1 are known or thought to be involved in chondrogenesis. For example, protein kinase A, which had the strongest effect on SOX9-dependent transcription in our assay (Table 1), has been found to induce phosphorylation of SOX9 on serine residues Ser 64 and Ser 181 and to enhance the activity of SOX9 with respect to the Col2a1 chondrocyte-specific enhancer (26). Our screening also identified SOX5 and SOX6, both of which are well known to be required in chondrogenesis.…”
Section: Discussionmentioning
confidence: 60%
“…Some genes listed in Table 1 are known or thought to be involved in chondrogenesis. For example, protein kinase A, which had the strongest effect on SOX9-dependent transcription in our assay (Table 1), has been found to induce phosphorylation of SOX9 on serine residues Ser 64 and Ser 181 and to enhance the activity of SOX9 with respect to the Col2a1 chondrocyte-specific enhancer (26). Our screening also identified SOX5 and SOX6, both of which are well known to be required in chondrogenesis.…”
Section: Discussionmentioning
confidence: 60%
“…However, it was not up-regulated but rather was down-regulated by hypoxia. Sox9 transcriptional activity has been reported to be enhanced by cAMP-dependent protein kinase A serine/threonine phosphorylation (63). We found that phosphorylation of Sox9 was not promoted but was suppressed by hypoxia (Fig.…”
Section: Terminal Differentiation Of Chondrocyte Is Suppressed By Hypmentioning
confidence: 57%
“…Like many other regulators, we speculated SOX9 is prone to posttranslational modifications which may impact its activity during adulthood and thereby possibly leading to its limited transcriptional capacity. For example, SOX9 was shown to be phosphorylated by PKA on serine 211 rendering its augmented DNA binding to the 18‐bp COL2A1 enhancer sequence (Huang et al ., 2000). TIP60 was first discovered to target SOX9 for acetylation by Hattori et al .…”
Section: Discussionmentioning
confidence: 99%